Inflammatory Arthritis and Heart Disease - Castaneda, Santos; Gonzalez-Juanatey, Carlos; Gonzalez-Gay, Miguel A. (Current Pharmaceutical Design, 2018)
Background: The term inflammatory joint disease (IJD) includes a group of chronic conditions, particularly rheumatoid arthritis (RA), ankylosing spondylitis (AS) and psoriatic arthritis (PsA), with predominant joint involvement and increased risk of cardiovascular (CV) complications and premature mortality. Objective: The study aims to review of the most relevant CV manifestations from clinical point of view associated with IJD. Methods: To update the current knowledge on CV manifestations in patients with IJD, we review the most relevant literature studies published in English (PubMed database) from January 2007 to February 2017. Results: Ischemic heart disease and congestive heart failure are the most relevant complications and those causing higher mortality. Pericarditis and myocarditis may be seen in patients with RA, especially in flares of disease, although they are often asymptomatic. Left ventricular diastolic ventricular dysfunction is an increasing recognized problem. Arrhythmias and cardiac conduction disturbances may be observed in patients with IJD. Chronic inflammation and fibrosis of the cardiac conduction system may be responsible for these complications. Noninvasive diagnostic tools including cardiac magnetic resonance imaging and echocardiography have improved considerably our understanding of the cardiovascular disease in IJD. Conclusion: Cardiac manifestations in IJD are frequent and they are the leading cause of an increased morbimortality in IJD. Clinicians would be aware of that, given that early diagnosis of these complications may reduce the frequency of CV events and improve survival of patients with IJD.
Keywords: rheumatoid arthritis